Biogeochemical Investigations of Terrestrial, Freshwater, and Wetland Ecosystems Across the Globe 2004
DOI: 10.1007/978-94-007-0952-2_29
|View full text |Cite
|
Sign up to set email alerts
|

Nitrous Oxide Emissions from Two Riparian Ecosystems: Key Controlling Variables

Abstract: Abstract. Nitrous oxide (N20 ) emissions were measured weekly to fortnightly between April 2001 and March 2002 from two riparian ecosystems draining different agricultural fields. The fields differed in the nature of the crop grown and the amount of fertiliser applied. Soil water content and soil temperature were very important controls of N20 emission rates, with a 'threshold' response at 24% moisture content (by volume) and 8°e, below which N20 emission was very low. N20 fluxes were higher at the site that h… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

1
5
0

Year Published

2004
2004
2022
2022

Publication Types

Select...
6

Relationship

1
5

Authors

Journals

citations
Cited by 7 publications
(6 citation statements)
references
References 27 publications
1
5
0
Order By: Relevance
“…The temporal variation of N 2 O fluxes in our study area was consistent, for example, with temperate climate riparian zones [ Machefert et al , 2004]. High fluxes occurred from June to September, accounting for about 50–60% of the annual emission in our study.…”
Section: Discussionsupporting
confidence: 86%
See 1 more Smart Citation
“…The temporal variation of N 2 O fluxes in our study area was consistent, for example, with temperate climate riparian zones [ Machefert et al , 2004]. High fluxes occurred from June to September, accounting for about 50–60% of the annual emission in our study.…”
Section: Discussionsupporting
confidence: 86%
“…In our study, the eulittoral zone accounted for about 2–30% of total littoral zone area, while N 2 O fluxes from that area accounted for about 45–78% of the total emissions each month. Highest fluxes in areas with the fluctuating water table were previously observed in the Great Ouse River catchment (U.K.) [ Machefert et al , 2004]. Altering wet/dry condition is an essential physical attribute of this zone that provided optimum conditions for coupled nitrification‐denitrification.…”
Section: Discussionmentioning
confidence: 99%
“…These results were compared with those from other studies in the literature. In a previous paper (Machefert et al, 2004), soil moisture was shown to be the main driving control on N 2 O emission from Chicheley, with soil temperature and dissolved organic carbon of secondary importance. Nitrate was rarely if ever limiting in this well-fertilised site.…”
Section: Data Analysesmentioning
confidence: 93%
“…Large spatial and temporal variability exists in soil denitrification and N 2 O fluxes (e.g., hot spots and hot moments, Groffman et al 2000;Machefert et al 2004;Hunt et al 2007;DeSimone et al 2010). While numerous studies have investigated N 2 O production in the laboratory (e.g., Hunt et al 2007), uncertainties remain in N 2 O fluxes when influenced by the interaction of multiple environmental factors in the field setting.…”
Section: Anthropogenic Activity Has Drastically Altered the Global Nimentioning
confidence: 99%